MANFAAT PENAMBAHAN LATIHAN OTOT DIAFRAGMA PELVIS PADA LATIHAN OTOT ABDOMEN TERHADAP DISMENORE PRIMER PADA REMAJA PUTRI - Eka Saputri, Maya Febriana; Nurjanah, Septi; Purwidiyanti, Sari; Maghfiroh, Laelatul; ., Ernawati (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
Abstract: The Benefits of Exercise to the Pelvic Diaphragm Muscles of Primary Dysmenorrhea in Adolescent Girls . Primary dysmenorrhea often occurs at the age of 25 years and not because of a gynecological condition, while secondary disease probems associated with gynecological conditions. Most teens deal with this by taking drugs or curative. In the research will provide a simple alternative therapies, easy to do and preventive. Objective : The purpose of this study was find out to know the benefits of exercise to the pelvic diaphragm muscles of primary dysmenorrhea in adolescent girls SMP N 1 Jeruklegi class VII. Methods : The study was conducted from May to July 2013, using a design Experimental research with cross sectional approach. Sampling was conducted in total sampling. The samples in this study were 70 young women. Analysis of test results using a paired T-test is a simple T-test for hypothesis 1 and 2, for the 3 hypotheses using independent t-test. The results showed that there were differences in pain between exercises I and II exercises that can be viewed from different variants. Variances different if P <0.05 Levene's test views of which 0062 (ie> 0.05), so that the same variant. Equal value means that 0.000 <0.005. So there is a difference between the benefits of exercise I and II. In practice that uses two ways obtained lower levels of pain.Keywords: Dysmenorrhea, youth, strengthening exercises abdominal muscles & diaphragm